2019
DOI: 10.1016/j.jbi.2019.103154
|View full text |Cite
|
Sign up to set email alerts
|

Patient data discovery platforms as enablers of biomedical and translational research: A systematic review

Abstract: Background The global shift from paper health records to electronic ones has led to an impressive growth of biomedical digital data along the past two decades. Exploring and extracting knowledge from these data has the potential to enhance translational research and lead to positive outcomes for the population's health and healthcare. Objective The aim of this study was to conduct a systematic review to identify software platforms that enable discovery, secondary use and interoperability of biomedical data. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The development of this platform will empower public health organizations, research groups, and industry bodies to answer key questions about the COVID-19 pandemic and its effects on human health in a streamlined timely manner, as has been needed for EHRs for many years [15,21]. The solution enables rapid cohort-building data discovery across data partners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of this platform will empower public health organizations, research groups, and industry bodies to answer key questions about the COVID-19 pandemic and its effects on human health in a streamlined timely manner, as has been needed for EHRs for many years [15,21]. The solution enables rapid cohort-building data discovery across data partners.…”
Section: Discussionmentioning
confidence: 99%
“…The need for more streamlined and efficient methods for discovering and analyzing EHRs is not new [15], but the COVID-19 pandemic has played a catalytic role in highlighting the need for these methods more than ever before. Data are federated when held at different locations and often hosted by different data controllers.…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties in data and technology discovery are also major barriers to data and technology reuse. In terms of data discovery, a systematic review to identify existing software that enable healthcare data discovery has revealed that healthcare/biomedical data discovery software is in great necessity, and current healthcare is already impacted by the ability to find the right data source for secondary research 13 . Technology discovery in the sense that allows the developers to pick ready‐to‐use services to develop digital health applications is largely missing, and the reuse of existing technologies of digital health applications are happening mostly within the same organization 14 or relying on opensource projects, in which the user essentially copies opensource codes and create a replica owned and maintained by the user.…”
Section: Problem Analysismentioning
confidence: 99%